Two doses of Lactobacillus induced different microbiota profiles and serum immune indices in pigs - Dongyan Zhang; Sixin Wang; Guixia Li; Meixia Chen; Hui Liu; Haifeng Ji (Journal of Functional Foods, 2023)
We evaluated the changes in microbiota profiles and serum immune indices of growing pigs after dietary supplementation with two different doses of Lactobacillus reuteri ZLR003. Both Lactobacillus doses significantly affected the growth performance of pigs. Copy number/g feces showed that L. reuteri ZLR003 reached the gastrointestinal tract and accumulated, but the higher dose was excreted more. L. reuteri ZLR003 increased species richness and Bacteroidetes abundance. The abundances of Clostridium_sensu_stricto_1, Terrisporobacter, Blautia, Corynebacterium and Streptococcus were significantly lower, and those of Christensenellaceae_R-7_group, Rikenellaceae_RC9_gut_group, Bifidobacteriaceaeg_Bifidobacterium and Lactobacillus were significantly higher in both Lactobacillus-treated groups than in controls. Abundances of Clostridium_sensu_stricto_1, Terrisporobacter and Lactobacillus differed significantly between the high- and low-dose Lactobacillus-treated groups. The acetic, butyric, propionic, valeric and isovaleric acid concentrations were higher in both Lactobacillus-treated groups than in controls, and acetic and butyric acid concentrations were higher in the low-dose group than in the high-dose group. The Lactobacillus-treated pigs had increased serum immunoglobin G, immunoglobin M, interferon-γ, interleukin (IL)-2, IL-4 and IL-10 levels and a decreased tumor necrosis factor-α concentration compared with the control group. Serum levels of interferon-γ were increased, and serum IL-2, IL-4 and IL-10 levels were lower in the low-dose group than in the high-dose group. The increased Lachnospiraceae and decreased Terrisporobacter abundances were the core functional genera associated with the significantly affected immune indices in the present results. Our findings will help facilitate the use of Lactobacillus strains in pig production.